Sovereign finance in emerging markets - Sabbadini, Ricardo (2019)
Each essay in this doctoral dissertation relates to a recent feature of sovereign finance in emerging market economies. In each article, I extend a quantitative macroeconomic model of sovereign debt and default to answer a particular question. In the first chapter, I investigate whether it is better for emerging countries to issue external debt denominated in local or foreign currency using a model with real exchange rates and inflation. I show how the welfare comparisons between the two options of debt denomination depend on the credibility of the monetary policy. In the next essay, I analyze the joint accumulation of sovereign debt and international reserves by emerging countries\' governments. In this theoretical framework, international reserves are a form of precautionary savings that can be used to smooth consumption even after a sovereign default. Statistics calculated with simulated data from a model with partial sovereign default indicate that the combined acquisition of assets and liabilities is an optimal policy in this type of model. In the last chapter, I examine whether low international risk-free interest rates, as observed in developed countries since the most recent global financial crisis, lead to a search for yield - identified via lower spreads even under higher default risk - in emerging markets sovereign bonds. I find that the inclusion of loss averse foreign lenders, a trait highlighted by the behavioral finance literature, in a standard model of sovereign default generates this result.